thank you
Answer:
a) 3p + 3q
b) 3a^2 + 4
c) -4ab + 24a
d) 3 (x - 2)
e) 3x + 7y
f) (x + 1) (2x + 3)
g) x^2 + x - 6
h) 6x^2 - 31x + 18
i) -5^2 + 6x +2y + 6
j) 2x^3 + 11x^2 + 17x + 6.
I answered question 1
Hope that helps. x
Answer:
It means something mathematical
Step-by-step explanation:
The slashed zero glyph is often used to distinguish the digit "zero" ("0") from the Latin script letter "O" anywhere that the distinction needs emphasis, particularly in encoding systems, scientific and engineering applications, computer programming (such as software development), and telecommunications.
Answer:4 3/8
Step-by-step explanation: you add the full numbers together then you have to change the denominator of 3/4 to be /8 and what you do to the bottom you have to do to the top then you get 3 11/8 you then see how many 8 go into 11 to se if you need to add another full number and the numbers left over go back to the 8 making the awnser 4 and 3/8.
The solutions of the quadratic equation x² + 13 = 8x + 37 are x = 4 + 2√10 and x = 4 - 2√10.
The quadratic equation is defined as a function containing the highest power of a variable is two.
The given equation as:
x² - 8x + 13 = 37
Subtracting 37 from both sides, we get:
x² - 8x - 24 = 0
Now, we have the equation in standard form, so we can use the quadratic formula to find the solutions:
x = (-b ± √(b² - 4ac)) / 2a
Here, a = 1, b = -8, and c = -24.
Substitute these values into the quadratic formula, and we get:
x = (-(-8) ± √((-8)² - 4(1)(-24))) / 2(1)
x = (8 ± √(64 + 96)) / 2
x = (8 ± √160) / 2
x = (8 ± 4√10) / 2
Simplifying, we get:
x = 4 ± 2√10
Therefore, the solutions of the quadratic equation x² + 13 = 8x + 37 are x = 4 + 2√10 and x = 4 - 2√10.
Learn more about quadratic function here:
#SPJ3
Answer:
Step-by-step explanation: